Determination of the OH- Content in the aqueous phase of hardened cementitious materials by an empirical Leaching method - M. Castellote; M. C. Alonso; C. Andrade (Materiales de Construccion, 2002)
The most reliable method to determine the concentration of hydroxyl ions in the aqueous phase of hardened cementitious materials is the squeezing of concrete at high pressures. However, this method needs special equipment as well as a relatively high amount of sample to be carried out. In present research, the determination of the OH concentration in the concrete pore solution is undertaken by a leaching method in granulated samples. The experimental program has been made using mortars with 5 different binders and three different leaching solutions. In the treatment of the results, different phenomena (dilution + dissolution of solid phases) occurring during leaching have been taken into account until reaching the target values validated by comparison with those obtained by means of the high pressure technique. The agreement found is good enough, for every binder tested, in spite of the fact that fully understanding of the leaching mechanism is not achieved and that concentrations and not activities of the ions are taken into account in the calculations. Therefore, the method suggested is empirical at present stage.